1968
DOI: 10.1017/s0043174500047251
|View full text |Cite
|
Sign up to set email alerts
|

Incorporated Vernolate and Other Weed Control Treatments for Peanut Production

Abstract: Fifteen herbicidal treatments were evaluated for weed control effectiveness in peanut (Arachis hypogaeaL.) culture at three locations in the peanut production area of eastern North Carolina during 1964 and 1965. Delayed preemergence treatments of 4,6-dinitro-o-sec-butylphenol (DNBP) alone and in combination withO-(2,4-dichlorophenyl)O-methyl isopropylphosphoroamidothioate (DMPA) were superior to conventional herbicidal and non-herbicidal control methods as were single and multiple incorporated treatments ofS-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Until 1968, vernolate was labelled for weed control in peanuts solely as an incorporated treatment and farmer experience in the Southeastern Coastal Plain indicated that both peanuts and nutsedge varied considerably in reaction. In 1968, Upchurch et al reported significant or nearly significant yield reductions from single preplant-incorporated PDRH treatments of 2-5 and 5-0 lb/ac, and devised multiple PDRH application procedures, involving reduced doses totalling 1-5-3 lb/ac in three applications extending into the post-emergence period. While tolerance to vernolate may be improved by multiple applications, risk of disease may also be increased as a result of greater soil disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 1968, vernolate was labelled for weed control in peanuts solely as an incorporated treatment and farmer experience in the Southeastern Coastal Plain indicated that both peanuts and nutsedge varied considerably in reaction. In 1968, Upchurch et al reported significant or nearly significant yield reductions from single preplant-incorporated PDRH treatments of 2-5 and 5-0 lb/ac, and devised multiple PDRH application procedures, involving reduced doses totalling 1-5-3 lb/ac in three applications extending into the post-emergence period. While tolerance to vernolate may be improved by multiple applications, risk of disease may also be increased as a result of greater soil disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional methods of incorporating vernolate resulted in poor control of nutsedge, especially if dry conditions persisted for several weeks after application. As Upchurch et al (1968) indicated, disc harrows are the implements most commonly used for incorporation. The practical aspects are further complicated by variations in farm procedure which include differences in: (a) the type of harrow used; (b) the angling ofthe disc gangs; (c) the depth of penetration; (d) the speed of operation; and (e) the number of discings.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigation is usually by sprinklers. Most of the herbicides included in this programme were examined beforehand on a preliminary screening basis by various scientists in other countries or by the authors of this paper (Santelman, Matlock & Six, 1967;Peters & Lowance, 1971;Upchurch, Selman & Webster, 1968;Cargill & Santelman, 1971;Hill, Peeper & Santelman, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…, and Rud and Chappell (16) showed that dinoseb (2sec-butyl-4,6-dinitrophenol) effectively controlled weeds with no substantial injury to peanuts. However, mixtures of dinoseb with either naptalam N-l-naphthylphalamic acid) (22) or diphenamid (N,N-dimethyl-2,2-diphenylacetamide) (25) were generally more effective than dinoseb alone. Watson and Nation (23) showed the varying tolerance of peanut to dinoseb when applied as a postemergence spray.…”
mentioning
confidence: 99%